2016
DOI: 10.1007/s41061-016-0062-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Photoactive Materials by Sonication: Application in Photocatalysis and Solar Cells

Abstract: In recent years, a good number of methods have become available for the preparation of an important group of photoactive materials for applications in photocatalysis and solar cells. Nevertheless, the benefits derived from preparing those materials through unconventional approaches are very attractive from the green chemistry point of view. This critical review work is focused on sonication as one of these promising new synthetic procedures that allow control over size, morphology, nanostructure and tuning of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…8,9 Sonochemical-based methods use ultrasound irradiation to produce liquid phase reactions, induced by cavitation. 10 Electric field assisted-methods have shown that electric current enhances the kinetics of inter-diffusion processes in solid-state reactions. 11 In Spark Plasma Sintering (SPS), pulsed, high DC currents have been used for synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Sonochemical-based methods use ultrasound irradiation to produce liquid phase reactions, induced by cavitation. 10 Electric field assisted-methods have shown that electric current enhances the kinetics of inter-diffusion processes in solid-state reactions. 11 In Spark Plasma Sintering (SPS), pulsed, high DC currents have been used for synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic cavitation is found to be useful in many applications. The redox radicals have been used to generate functional nanomaterials and for the degradation of organic pollutants in an aqueous environment [6] , [7] , [8] , [9] , [10] . For example, synthesis of biofunctional polyphenolic nanoparticles has been reported for use in targeted drug delivery [11] .…”
Section: Introductionmentioning
confidence: 99%
“…34 However, the dissimilarity in the precursors' solubility often led to a low yield of the final product. 35,36 First, Kesari et al have reported the room temperature bulk synthesis of MAPI by ultrasound sonication. 35 Jang et al synthesized the MHPs; their observation reveals that solubility is the deciding factor, and precursors with the same solubility have been used for their syntheses.…”
Section: Introductionmentioning
confidence: 99%